Investigating the Influence of Experience on Language Assessment Literacy Development: The EFL Teachers' Voices - Anisa, Khairani Dian; Sumardi, Sumardi; Setyaningsih, Endang (Universitas Hamzanwadi, 2023)
Research in various educational settings reveals that in-service teachers often demonstrate a limited proficiency in language assessment literacy (LAL). Recognizing this, scholars have been investigating factors that might enhance LAL, particularly focusing on the role of experience. Despite this interest, the specific influence of experiential factors on LAL development remains relatively unexplored. Addressing this gap, our study utilized semi-structured retrospective interviews in a narrative inquiry framework to assess how experience impacts the LAL development of two Indonesian EFL teachers. Both teachers, equipped with Master's degrees and relevant assessment training, have differing lengths of teaching experience and work in distinct educational institutions. Our findings indicate that foundational LAL knowledge and skills acquired through language assessment courses (LACs) were further enhanced by additional training and practical application in teaching contexts. Both participants, despite their varied teaching tenures, showed similar patterns of LAL development. This progression appeared influenced by their educational backgrounds, positive attitudes towards assessment, and a shared commitment to refining their assessment practices. The study concludes with recommendations for language educators, EFL teachers, and areas for future research.